The Revenue Administration Gap Analysis Program : An Analytical Framework for Personal Income Tax Gap Estimation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2021)
It is generally difficult to measure revenue not collected due to noncompliance, but a growing number of countries now regularly produce and publish estimated revenue losses. Good tax gap analysis enables the detection of changes in taxpayer behavior by consistent estimates over time. This Technical Note sets out the theoretical concepts for personal income tax (PIT) gap estimation, the different measurement approaches available, and their implications for the scope and presentation of statistics. The note also focuses on the practical steps for measuring the PIT gap by establishing a random audit program to collect data, and how to scale findings from the sample to the population.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: National Government Expenditures and Related Policies; Personal Income Tax; Tax Administration; Tax Compliance; Tax Evasion and Avoidance